Strategic Perspective of Services Marketing - Dr. Veena Tewari; Sweetline Sujee Lawrance; Rima Solanki (International Journal of Engineering and Management Research, 2022)
According to reports and research, the services sector has emerged as one of the biggest employers across different world economies during the last two decades. As per the UNCTAD, November 2021, the services sector pulled out following the trend of an overall expansion, trade-in services. However, tourism is still below pre-pandemic ranks at 6 trillion in 2021. While analyzing the regional picture, trade growth persisted patchy in the third quarter of 2021, considering decreased regional differences in comparison to the first half of the year. In fact, the growth of the services sector’s output has led to employment growth in these economies. In present times, it is of utmost importance to manage services in a more strategic manner, so that economic stability turns into a sustainable feature for the service businesses. According to the Organisation for Economic Co-operation and Development (OECD) member countries, more than 70 percent of the employed labor force worked in the services sector in 2017; among high-income industrialized OECD member countries, except for Greece, this proportion exceeded 80 percent. With the advancement of technology, consumerism, digitalization, and never before consumer movements, the services sector has been witnessing drastic changes. Contrary to (Dacko, 2012) services marketing, now a day is not only an approach but is also a strategy to be pursued by all firms. Managers and executives of the Service industry should carefully adapt the marketing mix composition to identify the best services strategy to achieve their marketing and business objectives. To date services marketing has received little strategic attention in the services marketing literature. Most of the research in the service sector has been concentrated on SDL and service ecosystems. As per (Pomering & Johnson, 2018) it has been proposed that service organization has strengthened sustainability in terms of environment and society through decision making. This paper is an attempt to propose a model, considering the services as an integral part of any organization. The proposed model is relevant to organizations irrespective of the fact whether they offer tangible goods or intangible services or both in some proportion. The methodology adopted is qualitative and exploratory. Authors have reviewed extensive literature and coupled the same with monitoring of industry trends to come up with the model for service marketing. The model may be applied as a strategic tool, to design and allocate the marketing mix components for enhanced visibility in the market.